La trajectoire des savoirs citoyens : le cas du développement d’un projet minier québécois - Justine Lalande (VertigO)
Using an exploratory approach inspired by organizational ethnography, we follow the trajectory of citizen knowledge, that is its formation, recognition and finally, its integration into decisions. This text first proposes a typology of the formation of different types of citizen knowledge. To illustrate this trajectory of citizen knowledge, we use the case of a citizen mobilization contesting a mining development project in a small municipality in the province of Quebec, Canada. We conclude that despite the mobilization of different types of knowledge by citizens, the promoters are tempted to pursue a social acceptability approach rooted in the knowledge deficit model, which is relatively closed to the reception and integration of citizen knowledge. Finally, we propose strategies to overcome the knowledge deficit model in order to account for citizen knowledge in projects.